Pengaruh Kebiasaan Pikiran (Habits of Mind) terhadap Penguasaan Konsep Matematika - Nurmala Dewi Qadarsih (Universitas Indraprasta PGRI Jakarta, 2017)
This research aims to describe the effect of habits of mind on mathmematics concept mastery. The method used is survey method. The population of this research is Junior High School students in Depok. 3 school samples are selected to represent all students in Depok with total respondents of 92 students. The instrument used is the instrument of mathematical concept mastery consisting of 20 questions and Habits of Mind questionnaire. The result of the research indicates there is significant effect of habits of mind on mathematics concept mastery. The contribution of habits of mind to mathematics concept mastery is 27.67 %. This research can be recommended to improve the mathematics concepts mastery of Junior High School students by improving the habits of mind to students.